2021
DOI: 10.1002/esp.5084
|View full text |Cite
|
Sign up to set email alerts
|

A historical review of sediment export–import shift in the North Branch of Changjiang Estuary

Abstract: Net sediment transport is predominantly seaward in fluvial-dominated estuaries worldwide. However, a distributary branch in the Changjiang Estuary, the North Branch, undergoes net landward sediment transport, which leads to severe channel aggradation. Its controlling mechanism and the role of human activities remain insufficiently understood, although such knowledge is necessary for better management and restoration opportunities. In this study we revisit the centennial hydromorphodynamic evolution of the Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 38 publications
(66 reference statements)
2
20
0
Order By: Relevance
“…The shift from total sediment export to import can result from bathymetric changes (estuary deepening and narrowing; Figure 1b and c), as observed by Guo et al 23 . Nonetheless, it may also result from changes in river flow and wave forcing (Figure 2a and b).…”
Section: Comparison Of Annual Sediment Fluxes Between 1990-2000 and 2005-2015supporting
confidence: 56%
See 1 more Smart Citation
“…The shift from total sediment export to import can result from bathymetric changes (estuary deepening and narrowing; Figure 1b and c), as observed by Guo et al 23 . Nonetheless, it may also result from changes in river flow and wave forcing (Figure 2a and b).…”
Section: Comparison Of Annual Sediment Fluxes Between 1990-2000 and 2005-2015supporting
confidence: 56%
“…Human activities can drastically change the upstream river supplies (e.g., through dam construction ), the local sediment nature (e.g., through dredging activities 21 ), and the estuary morphology (e.g., through harbor extension and channelization 22 ). Guo et al 23 recently investigated a centennial hydro-morphodynamic evolution of the Changjiang Estuary (China) to highlight the influence of anthropogenic pressures on estuary sediment import-export. More specifically, they observed that a narrower funnel-shaped estuary resulting from intensive human activities induced a shift from ebb to flow dominated estuary, leading to increase sediment import and channel aggradation.…”
Section: Introductionmentioning
confidence: 99%
“…The shift from total sediment export to import has also happened in other systems (e.g., Changjiang Estuary 27 ) and can be the result of bathymetric changes (estuary deepening and narrowing; Fig. 1 b,c, Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 80%
“…4 i (i.e., 2nd period minus 1st period), characterizing more import (or less export) of mud in 2005–2015 than in 1990–2000. Such behavior can be attributed to human-induced changes, which impacted the system functioning via the estuary deepening and narrowing, as observed by Guo et al 27 . It is also supported by Grasso and Le Hir 26 who simulated an intensification of density-induced circulation due to bathymetric changes in the Seine Estuary from 1960 to 2010.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation